Charaterization of isolated potential lactobacilli and used as probiotic food (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
This research was carried out to isolate and identify lactobacilli from yogurt and vegetables sample from Dhaka, Bangladesh. Twenty five Lactobacillus strains were isolated and identified as Lactobacillus species based on cultural characteristics, biochemical tests, and sugar fermentation. The results showed only four among twenty five isolates were highly responded to probiotic criteria such as low pH tolerance (2.5), bile salt tolerance (2%), gastric juice tolerance (0.5% bile salt, 0.2% NaCl, 0.32% pepsin pH 2.5) in-vitro and were identified strains as Lactobacillus plantarum imy-21, Lactobacillus plantarumimy-22, Lactobacillus plantarum imv-26 and Lactobacillus acidophilus imy-37 according to Bergey's Manual of Systematic Bacteriology and 16s rDNA sequencing. All of the strains were showed protease activity on skim milk agar. These strains were sensitive to ampicillin, doxycycline, erythromycin and tetracycline; also have antimicrobial activity against enteric pathogen such as ATCC of Salmonella Enteritidis, Staphylococcus aureus, Listeria monocytogenes, Shigella flexneri, Bacillus cereus, Klebsiella pneumoniae and Escherichia coli (environmental isolates). Four isolated Lactobacilli strains were able to maintain their probiotic properties in freeze dried condition over 90 day’s storage. This study concludes that these strains may be used as potential candidate as probiotic food.Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 274-283